2021
DOI: 10.1038/s41398-021-01715-x
|View full text |Cite
|
Sign up to set email alerts
|

Secure attachment priming protects against relapse of fear in Young adults

Abstract: Previous studies have shown that activating the attachment system attenuates fear learning. This study aimed to explore whether attachment priming can also impact on fear extinction processes, which underpin the management of anxiety disorders. In this study, 81 participants underwent a standard fear conditioning and extinction protocol on day 1 and returned 24 h later for an extinction recall and reinstatement test. Half the participants were primed to imagine their closest attachment figure prior to undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…While the findings from the social support paired condition of this study cannot provide further insight into the effects of loneliness itself on fear learning, they do provide insight into whether social support, which has been shown to reduce fear acquisition ( Hornstein & Eisenberger, 2017 ; Toumbelekis, Liddell, & Bryant, 2018 ) and improve fear extinction in those who are not specifically lonely ( Hornstein et al, 2016 ; Hornstein et al, 2018 ; Toumbelekis, Liddell, & Bryant, 2021 ), is similarly able to improve fear extinction in those who are lonely. Thus, we next examined the effects of the social support paired condition in order to understand whether social support might ameliorate the effect of loneliness on fear learning.…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…While the findings from the social support paired condition of this study cannot provide further insight into the effects of loneliness itself on fear learning, they do provide insight into whether social support, which has been shown to reduce fear acquisition ( Hornstein & Eisenberger, 2017 ; Toumbelekis, Liddell, & Bryant, 2018 ) and improve fear extinction in those who are not specifically lonely ( Hornstein et al, 2016 ; Hornstein et al, 2018 ; Toumbelekis, Liddell, & Bryant, 2021 ), is similarly able to improve fear extinction in those who are lonely. Thus, we next examined the effects of the social support paired condition in order to understand whether social support might ameliorate the effect of loneliness on fear learning.…”
Section: Methodsmentioning
confidence: 63%
“…Thus, reminders of social support figures (via images) or the experience of physical warmth (which has been shown to be a critical component in feelings of social connectedness: Williams & Bargh, 2008 ; Bargh & Shalev, 2012 ; Inagaki & Eisenberger, 2013 ), may reduce these perceptions of being socially disconnected in the moment. However, given that viewing images of or thinking about social support figures ( Hornstein et al, 2016 ; Hornstein et al, 2018 ; Hornstein et al, in prep ; Toumbelekis et al, 2021 ) and holding physically warm objects ( Hornstein et al, 2021 ) have been shown to bring about enhanced extinction in populations that were not specifically lonely, it is also possible that these cues may counteract the effects of loneliness simply by enhancing extinction processes and not by reducing loneliness itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our sample, children’s ratings of parental warmth were very high and showed relatively little variability. Consequently, more in-depth longitudinal investigations with measures spanning cellular to functional systems levels are warranted to elucidate the buffering role of parent–child relationship quality, including parental warmth and responsiveness 79 . Mounting evidence testifies to the profound impact of parenting on child development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cellular aging indices would allow inquiries into how pre-/perinatal stressors (e.g., malnutrition, maternal traumatic experiences/inflammation) can interact with the offspring's genetic profile to shape their lifespan development, including biological aging rate and, thus, potentially their resilience against later life adversity ( Chan et al, 2019 ;Goldstein et al, 2021 ;Krontira et al, 2020 ;Mareckova et al, 2020 ;Ramo-Fernandez et al, 2021 ). Seventh, there is compelling evidence that personal characteristics, such as sense of purpose, sprituality, and social-affective enrichment in the form of warm parenting in childhood/adolescence and supportive close relationships later in life can alleviate the sequelae of prior adversity exposure ( Bowes et al, 2010 ;Feder et al, 2009 ;Gee, 2021 ;Gunnar et al, 2019 ;Kiecolt-Glaser et al, 2020 ;Luby et al, 2020 ;Manvelian and Sbarra, 2020 ;Sbarra and Coan, 2018 ;Toumbelekis et al, 2021 ). As such, more in-depth investigation of the unique mechanisms through which distinct intra-and interpersonal factors may protect against the malign effects of stressful life experiences would be worth pursuing in the future.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%